2021
DOI: 10.1016/j.eats.2021.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Arthroscopy-Assisted Reduction and Internal Fixation (ARIF) of Tibial Rim Fracture With Posterior Cruciate Ligament Reconstruction and Repair of Posterolateral Complex and Meniscal Injury

Abstract: Multiligament knee injury with periarticular fractures are high-velocity injuries and generally require a staged treatment approach that involves multiple hospitalizations and results in delayed return to activity. We report a singlestage management technique for these injuries with arthroscopy-assisted reduction and internal fixation of a depressed tibial rim fracture with concomitant posterolateral complex repair, medial meniscal repair, and posterior cruciate ligament reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, this injury mechanism does not account for every case. In some literatures and in our cases, there have been large tibial plateau fractures, that are more than 25% of anteroposterior length of the medial tibial plateau, co-occurred with PCL and PLC injuries [ 7 , 17 ]. This atypical presentation may be related to the intensity of the trauma.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, this injury mechanism does not account for every case. In some literatures and in our cases, there have been large tibial plateau fractures, that are more than 25% of anteroposterior length of the medial tibial plateau, co-occurred with PCL and PLC injuries [ 7 , 17 ]. This atypical presentation may be related to the intensity of the trauma.…”
Section: Discussionmentioning
confidence: 98%
“…However, arthroscopic techniques were not used in these cases. In 2021, Sundararajan et al [ 17 ] reported single-stage surgery for these injuries with ARIF of a tibial rim fracture with PLC repair and PCL reconstruction, but the efficacy of the patient's postoperative recovery was not described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation